The Polysemy and Hyponymy of Mandarin Spatial Prepositions and Localisers: Building Semantic Maps from the Ground up - Ursini, Francesco-Alessio; Rao, Qi; Zhang, Yue Sara (Frontiers in Communication, 2021)
The goal of this paper is to offer an overview of polysemy patterns in Mandarin’s chief spatial categories: prepositions (e.g., zai) and simple and compound localisers (respectively, qian and qian-mian). The paper presents data from an elicitation study that shows how speakers can access multiple senses and hyponymy relations for the vocabulary items belonging to these categories. The paper shows that while prepositions can potentially cover different spatial relations in the opportune context (e.g., zai “at”), localisers select increasingly specific senses (e.g., qian “front” and qian-mian “front side”). The paper also shows how speakers can access hyponym-like sense relations emerging from these patterns (e.g., qian-bian covering a more specific sense than qian). Semantic dimensions such as “distance” and “location type” determine the strength of these hyponymy relations. The paper offers an account of these data based on the “semantics maps” model, which captures polysemy and hyponymy patterns via the clusters of locations they refer to. It is shown that this novel model is consistent with previous works on the polysemy of spatial categories and sheds light on how Mandarin offers a unique organisation of this domain.